Study on penetration characteristics of high-speed elliptical cross-sectional projectiles into concrete. (October 2019) - Dong, Heng; Liu, Zihao; Wu, Haijun; Gao, Xudong; Pi, Aiguo; Huang, Fenglei
Highlights: Penetration of rigid, elliptical projectiles into concrete were investigated. LS-DYNA 3D analysis determined cavity surface stress characteristic in numerical simulations. The elliptical cross-section projectiles had good penetration behavior and trajectory stability. A formula was proposed to predict the penetration depths of the elliptical projectiles. Abstract: A series of concrete target penetration tests were conducted using one type of circular cross-section projectile and two elliptical cross-section projectiles with shape ratios of 1.5 and 2.0, all with the same mass, length, and cross-sectional area. In the experiments, the projectiles were launched with an initial velocity from 700 to 1100 m/s. The failure characteristics of the targets, penetration depths, crater depths, and projectile mass losses were measured after the tests. The results indicated that elliptical cross-section projectiles also have good penetration performance and trajectory stability compared with the circular cross-section projectile. To further explore the mechanism governing the penetration of elliptical cross-section projectiles into concrete and the stress characteristics on the projectile nose, six projectile models with different shape ratios (1.0, 1.2, 1.4, 1.6, 1.8, and 2.0) were established using the commercial finite element software LS-DYNA. The relationship between the normal stress and normal velocity of different elements on the surface of the projectile nose were obtained. The results showed that the normal stress on the elliptical cross-section projectile nose increased gradually from the minor axis to the major axis. A formula based on dynamic cavity expansion theory and the stress characteristics on the projectile nose was accordingly proposed, that can be used to predict the penetration depth of elliptical cross-section projectiles.